Carrière non traditionnelle: le cheminement et le vécu de certaines femmes qui ont choisi cette option - Fournier, Genviève; Pelchat, Diane (Canadian Journal of Counselling and Psychotherapy, 2011)
The purpose of this article is to present the main results of an exploratory study concerning career process and actual experiences of women working in a non-traditional field as television producers. We will present the answers that eight women producers gave to an open questionnaire concerning vocational choice, life at work and effects of professional success on their identity. Results analysis suggest a discussion raising five major questions from which we propose some elements of reflection that should help towards a better understanding of what they actually go through while working in a non-traditional field. It should also help in the development of practices in career counseling concerning women.